Diachronic multimodality research – a mini-review - Pflaeging, Jana (Frontiers in Communication, 2024)
This mini-review gives an overview of diachronic multimodality research, an approach that multimodality scholars have pursued only rarely so far. Acknowledging the comparably large share of case studies in this line of research, this paper sets out by surveying empirical contributions. Many of them also provide discussions of selected theoretical and methodological aspects, which are subsequently collated and complemented with concepts from a number of more extensive theoretical proposals. Identifying main developments in diachronic multimodality studies and avenues for future work, this review seeks to support its growth into a mature research strand with a solid theoretical basis, a versatile methodological toolbox, and a broad range of research objects.